Improving ergonomics for the bedside assistant in robotic colorectal surgery. Issue 1 (24th January 2023) - Wong, Shing Wai; Ang, Zhen Hao; Crowe, Philip
Abstract: The aim of the study was to document when significant bedside assistant (BA) and robotic arm collisions occurred during robotic colorectal surgery (RCS). An observational study of 10 consecutive RCS cases, from May 2022 to September 2022, was performed. Situations when there was significant collision between BA arm and robotic arm (to cause inadvertent movement of the assistant instrument) were documented. The assistant port was randomly placed to the right or the left side of the camera port. Situations which led to detrimental BA ergonomics include dissection at the most peripheral working field, proximity of the target (mesenteric vessels), small bowel retraction, placement of the assistant port in the medial position (on the left side of the camera port), during intra-corporeal suturing and robotic stapler use. The robotic console surgeon can predictably identify and avoid situations when injury to the BA may occur.